Topeng Surakarta Sebagai Sumber Ide Penciptaan Motif Batik Pada Busana Casual Wanita - Kristanti Kristanti; FP. Sri Wuryani (Texture:Art and Culture Journal, 2021)
The main idea behind the creation of this artworks is inspired by the visual form of the Surakarta masks. This concept was chosen because the Surakarta masks has a variety of shapes, colors, functions, and characters that are different and interesting for the source of ideas for the creation of batik motif, such as the masks of Panji Inu Kertapati, Dewi Sekartaji, Klana Sewandana, Gunungsari, and Jaya Kartolo. This final project aims to create women's casual outfit by applying the Surakarta masks as the basic idea in creating the artworks. The Surakarta mask's scope gives rise to ideas to be developed into the creation of written batik motif. The process of creating works starts from the exploration stage, which is observing the shape of the Surakarta masks and then pouring it into the design stage of an alternative design to be selected as a batik motif to be applied to casual outfit. The last stage is the embodiment stage, in this process starting from making a dress pattern, painting on a patterned fabric for casual cloth, batik, painting dyeing, sewing and finishing. The coloring technique used in the creation process is the technique dabbing using remasol dyes. The materials and tools used were wax, canting, remasol, waterglass, silk cotton, and satin fabric bridal. As the result of my final project, there are 5 women's casual outfits, each named according to the characters of the Surakarta mask. The first artworks entitled Lelanange Jagad (Handsome Man), the second entitled Kirana (Moonlight), the third entitled Ahengkara (Roam), the fourth entitled Sajjana (Immortal), and the last artworks entitled Warada (Strong). This design results an innovation to preserve Surakarta mask art culture and also the traditional art of batik in the fashion sector.